Freud’s father religion: refinding Moses and Monotheism in 2023 - Titelman, David (Frontiers in Psychology, 2026)
At the inauguration of the Sigmund Freud chair of psychology at the Hebrew University in Jerusalem 1977, Anna Freud said that the rejection of psychoanalysis as a Jewish science “today can be regarded a title of honor.” The historian E. Roudinesco later discarded this claim as a “racist appropriation,” contrasting it with Edward Said’s allegedly anti-colonial reading of Freud’s major work on Judaism, Moses and Monotheism. Said’s in truth affectionate embrace of Freud’s Moses, however, influenced my openness to the book after October 7, 2023, and inspired the psychoanalytic re-reading of it that is the gist of this paper. Freud’s vacillation in publishing Moses in 1939 is scrutinized, as is his life-long combined professed godlessness and proud identification as a Jew. The discussion covers Freud’s interactions with colleagues and other interlocutors, which influenced his views on religion and antisemitism, and the extensive secondary literature on these and related issues. The ensuing understanding of Freud’s Moses is that it represents a self-analytic tour de force in which his father Jakob Freud, who until his death remained piously attached to traditional Judaism while also open to the Jewish Enlightenment, stands out as a profoundly impactful presence in Freud’s soul as well as in his legacy to the world.